A class of distributions with the quadratic mean residual quantile function. Issue 19 (2nd October 2019) - Sankaran, P. G.; Dileep Kumar, M.
Abstract: The present paper introduces a new family of distributions with quadratic mean residual quantile function. Various distributional properties as well as reliability characteristics are discussed. Some characterizations of the class of distributions are presented. The estimation of parameters of the model using method of L -moments is studied. The practical application of the class of models is illustrated with a real life data set.